Effect of earthing material water content on the resistivity and corrosion behaviour of earthing electrode - Arina Fatin, Hasan (2018)
Electrical earthing systems main purposes is to disperse flow of charge to mother earth within the shortest time possible at the event of lightning or fault. Low frequency of earthing resistance of an electrical earthing systems determine its efficiency. Thus, there have been enormous amount of studies conducted on various material in order to find the best performing materials for an earthing systems. This study aims to determine the effect of varying water content on the electrical resistivity of earthing materials, determining the effect of suction on the corrosion behavior of copper and aluminium electrodes buried under earthing materials as well as identifying the type of corrosion induced microbes in earthing materials that is responsible for the corrosion of the earthing electrode. Two sample were used in this study namely Andrassy bentonite and Marconite. The sample electrical properties were studied by Wenner-four point test. The sample soil-water characteristic curve (SWCC) was established by Vapour Equilibrium Technique (VET). The sample biological characteristics was determined by means of spread plate method. The study outcome indicates that Andrassy Bentonite electrical resistivity is highly affected by water presence while Marconite electrical resistivity does not affected by the water presence. Aluminium and copper electrode corrosion behaviour is not affected solely by the water content of the earthing material, instead it is governs by a few other factors such as surrounding environment, sulphur content, pH, the presence of microorganisms and etc. One species of bacteria (i.e. Micrococcus luteus) and four species of fungus (i.e. Paecilomyces lilacinus, Trichoderma atroviride, Fusarium proliferatum, and Rhodotorula mucilaginosa) are the corrosion induced microbes that is responsible for corrosion of earthing electrode, identified in this study.